Study on Fumigant and Contact Toxicity of Catharanthus roseus Against Sitophilus oryzae - S, Abdul Majeed. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Background & objectives: In view of the recently increased interest in developing plant origin insecticides as an alternative to chemical insecticide, this study was undertaken to assess the fumigant and contact toxicity of crude aqueous extract of Catharanthus roeus leaf (Apocynaceae) against larvae and adult Sitophilus oryzae. Methods: Leaves were collected and dried crude aqueous extract of Catharanthus roeus leaf was done with Soxhlet?óÔé¼Ôäós extractor in distilled water for 8 hrs. Extracts were concentrated using rotary evaporator (BUCHI B-850) under reduced pressure at 60?é??C. Bioefficacy of crude aqueous extract of Catharanthus roeus leaf was evaluated under laboratory conditions using 10, 14 and 18th day larvae and adult Rice weevil. Results: The fumigant and contact toxicity of crude aqueous extract of Catharanthus roeus leaf exhibited higher toxicity against rice weevil. After 24 hours of exposure period fumigant and contact toxicity LD50 values were 0.027 mg cm-2 and 0.083 mg cm-2 respectively. Interpretation & conclusion: From the results it can be concluded that the larvae and adult rice weevil were susceptible to crude aqueous extract of Catharanthus roeus leaf. Such findings would be useful in promoting research aiming at the development of new bio-insecticides for rice weevil control based on bioactive chemical compounds from Catharanthus roeus leaf an alternative to chemical insecticides.